2015
DOI: 10.1002/pssb.201552051
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline bismuth films: Correlation between grain structure and electron transport

Abstract: , Phone: þ375 29 577 28 00, Fax: þ375 17 209 54 45Grain structure and the temperature dependences of resistivity, magnetoresistance, Hall and Seebeck coefficients measured in the range from 4 to 300 K were investigated for polycrystalline bismuth films obtained by the melt spinning (MS) and electrochemical deposition (ECD) methods. Charge-carrier concentration and mobilities were calculated assuming the carrier scattering on acoustic deformation potential as the dominant scattering mechanism, parabolicity of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…α lies in range (1-2)×10 5 W/m 2 K, the difference in media and melt temperature was about 400 K. All the other parameters were taken as for pure Bi. Therefore, estimated cooling speed was 10 6 -10 7 (K s) −1 as in work [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…α lies in range (1-2)×10 5 W/m 2 K, the difference in media and melt temperature was about 400 K. All the other parameters were taken as for pure Bi. Therefore, estimated cooling speed was 10 6 -10 7 (K s) −1 as in work [33].…”
Section: Discussionmentioning
confidence: 99%
“…The rMR temperature dependencies of doped samples (2)-(6) are not monotonous. The well-known expression [23,33,40,41] for rMR establishes the square dependence on the carrier's mo-…”
Section: Conductivity Type Changementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, research on the preferred orientation of Bi thin films has made some progress (Marcano et al, 2010(Marcano et al, , 2013Liao et al, 2014;Fedotov et al, 2015Fedotov et al, , 2016. Wu found that Bi thin films with (111) preferred orientation could be obtained on glass substrates at temperatures ranging from À40 to 93 C via pulse laser deposition, while the orientation was random when the substrate temperature rose to 200 C (Wu & Chern, 2008).…”
Section: Introductionmentioning
confidence: 99%